Maternal engagement in infant’s prevention and control of anemia with micronutrients. District of Independencia, Lima – 2015 - Lozano-Villafuerte, Lorena (2019)
Objective: To identify the level of maternal engagement in complying with the micronutrient (MN) supplementation guidelines for the prevention and control of anemia in children under 24 months of age "in the district of Independencia, Lima, between the years 2015 and 2016". Materials and methods: A descriptive, observational, longitudinal and retrospective study was performed at the Centro de Salud Ermitaño Bajo, district of Independencia, Lima, between the years 2015 and 2016. Participants were mothers whose children started micronutrient supplementation. Data was collected from 40 selected medical records. Data analysis was performed using descriptive statistics. Main outcome measures were: I) High level of engagement: the infant received ≥ 181 MN sachets and ≥ 2 hemoglobin doses. II) Intermediate-high level of engagement: the infant received ≥ 181 MN sachets and ≤ 1 hemoglobin dose. III) Intermediate-low level of engagement: the infant received ≤ 180 MN sachets and ≥ 2 hemoglobin doses. IV) Low level of engagement: the infant received ≤ 180 MN sachets and ≤ 1 hemoglobin dose. Results: I) High level of engagement: 9 mothers (22.5 %). II) Intermediate-high level of engagement: 3 mothers (7.5 %). III) Intermediate-low level of engagement: 5 mothers (12.5 %). IV) Low level of engagement: 23 mothers (57.5 %). Conclusions: Only 9 (22.5 %) mothers had a high level of engagement in complying with the micronutrient supplementation guidelinesfor the prevention and control of anemia in children under 24 months of age at the Centro de Salud Ermitaño Bajo, district of Independencia.